Harmonization of Tri Hita Karana: A Sustainable Tourism Branding Strategy (Grand Istana Rama Study) - I Gede Novara Krishna; Ragil Noviyanti; Shigit Januar (Lektur: Jurnal Ilmu Komunikasi, 2025)
This study aims to evaluate the marketing communication strategy of Grand Istana Rama Hotel (GIR) in Kuta, Bali, and to address the research gap regarding local wisdom as a core strategic asset rather than mere ornamentation in sustainable tourism. Employing a qualitative single case study method and in-depth interviews with key management, this research analyzes how GIR radically integrates the Tri Hita Karana (THK) philosophy into its brand equity through the strategic transformation of cultural capital. The process involves examining three strategic pillars: Palemahan (environment), transformed into a 1.7-hectare "Green Oasis" USP defying high-density economic logic; Parhyangan (spirituality), leveraged for brand trust through ritual transparency and ethical boundaries; and Pawongan (social), fostering strong emotional bonds through a humanist service culture amidst industry automation. Netnographic data from guest reviews validates that the human-centric service and the tranquil atmosphere are the primary drivers of customer loyalty and positive perception. The results show that this fundamental THK integration functions as a counterintuitive competitive defense mechanism, effective against market saturation and the impending 2025 hotel moratorium. The conclusion is that fundamentally integrated local wisdom offers a resilient and authentic model, positioning THK as a strategic communication framework that generates superior functional, psychological, and ethical value for sustainable tourism development.